Cholesterol oxides: occurrence in foods, formation and biological effects (Revista Brasileira de Ciências Farmacêuticas, 2002)
Important points involving the occurrence of cholesterol oxides -COs- in foods, formation mechanisms and biological activities of these compounds associated to cytotoxic, angiotoxic, atherogenic, mutagenic and carcinogenic processes were reviewed. The individual and/or total COs levels detected in foods were considered of potential risk for health. It was also considered necessary to determine the implication of COs from dietary sources in relation to endogenous COs formed metabolically. Inhibition of the cholesterol oxidation in foods to prevent the ingestion of these oxides was emphasized.